2007
DOI: 10.1253/circj.71.1977
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-Remodeling Effects of Angiotensin II Type 1 Receptor Blocker in a Canine Atrial Fibrillation Model

Abstract: trial fibrillation (AF) is one of the most common arrhythmias, but is still difficult to treat because of its complicated electrophysiological and pathological properties. 1 AF itself causes electrical and structural changes, which are called electrical and structural remodeling, and these changes are favorable for the maintenance of AF. [2][3][4][5][6] Previous studies have shown that structural abnormalities can induce conduction heterogeneity, which promotes local reentry and leads to the development of AF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 31 publications
(50 reference statements)
4
26
3
Order By: Relevance
“…13 Third, the ECV group included a much higher percentage of those who had hypertension and had more usage of ACEIs or ARBs than the ABL group, and these medications are likely to have had salutary effects on LA function and remodeling. 26 However, in our data, receiving ACEIs or ARBs did not significantly influence the reverse remodeling of the LA after ABL and ECV. The other limitation was that there was no baseline assessment of Doppler and tissue Doppler parameters because of the difficulty in taking measurements in patients with PeAF before the procedures.…”
Section: Study Limitationscontrasting
confidence: 67%
“…13 Third, the ECV group included a much higher percentage of those who had hypertension and had more usage of ACEIs or ARBs than the ABL group, and these medications are likely to have had salutary effects on LA function and remodeling. 26 However, in our data, receiving ACEIs or ARBs did not significantly influence the reverse remodeling of the LA after ABL and ECV. The other limitation was that there was no baseline assessment of Doppler and tissue Doppler parameters because of the difficulty in taking measurements in patients with PeAF before the procedures.…”
Section: Study Limitationscontrasting
confidence: 67%
“…25 The findings in the present study suggested that RASIs might be effective in patients with a less fibrotic LA. Although many studies have shown that blocking the renin-angiotensin-aldosterone system leads to the prevention or inhibition of fibrosis, [26][27][28][29] it has not been demonstrated whether RASIs can pathologically reverse or normalize established fibrosis. This study may suggest that RASIs may suppress AF recurrences after PVI when the LA has not yet developed severe structural remodelling.…”
Section: La Size and Fibrosismentioning
confidence: 99%
“…The activation of stretch-activated channels contributes to depolarization of the membrane potential, shortened refractoriness, slowed conduction, and increased spatial dispersion. 54 Several types of SAC have been described in the cardiac cell: potassium-selective channels, 55 chloride-selective anion channels, 56,57 and non-selective cation channels. 58 Bode et al showed that atrial fibrillation potentiated by dilatation in rabbit heart can be inhibited by blocking SAC with GsMTx4, a peptide isolated from tarantula venom and the first specific reagent for non-selective cation SAC.…”
Section: Trp Channels Participate In Arrhythmogenesismentioning
confidence: 99%